2013
DOI: 10.1038/sc.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer in individuals with spinal cord injuries

Abstract: Study design: Prospective scoping review. Objectives: To conduct a scoping review of all the literature related to bladder cancer in individuals with spinal cord injuries (SCI). Methods: Literature search of the databases Pubmed, CINAHL, ProQuest, PsychINFO and Scopus up to and including August 2012. Articles related to bladder cancer among SCI patients were identified, and data pertaining to epidemiology, risk factors, screening, prevention and management was reviewed and summarized. Results: An association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 45 publications
(149 reference statements)
5
51
0
6
Order By: Relevance
“…This finding corresponds with numerous prior studies that reported a range of 16 to 34 years from injury to time of diagnosis. 5 Our nonsignificant finding for those with a SCI of less than 10 years is also consistent with a recent Taiwanese cohort study that followed 54,401 patients with SCI for an average of 6 years (range less than 1 to 13 years) and found no increased risk of bladder cancer diagnosis compared with the nonSCI control group. 20 These findings imply a dose-response relationship between potential SCI related risk factors and bladder cancer.…”
Section: Years Since Injurysupporting
confidence: 92%
See 2 more Smart Citations
“…This finding corresponds with numerous prior studies that reported a range of 16 to 34 years from injury to time of diagnosis. 5 Our nonsignificant finding for those with a SCI of less than 10 years is also consistent with a recent Taiwanese cohort study that followed 54,401 patients with SCI for an average of 6 years (range less than 1 to 13 years) and found no increased risk of bladder cancer diagnosis compared with the nonSCI control group. 20 These findings imply a dose-response relationship between potential SCI related risk factors and bladder cancer.…”
Section: Years Since Injurysupporting
confidence: 92%
“…4 Prior studies found that bladder cancer develops in people with SCI earlier than normal, at a mean age of 48 to 61 years, 5 and about 24% were diagnosed at less than 40 years old. 13 Our finding of a SMR of 20 in patients with SCI age 30 to 59 years is largely consistent with previous studies, and suggests that patients with SCI are exposed to risk factors earlier or to risks that are more pernicious.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…The production of oxygen species in inflamed tissues has also been shown to promote the formation of mutations in cancer cells. Inflammation of the urethra and bladder is seen in infection, like schistosomiasis, but there are several non-infectious causes, including benign prostatic hyperplasia (BPH), extended use of indwelling catheters and bladder, kidney and ureter stones [14,1619]. Both schistosomiasis and indwelling catheters are believed to promote the development of bladder cancer due to the induction of epithelial hyperplasia, which results from chronic irritation (Figure 1).…”
Section: Inflammation In Pathogenesis Of Bladder Cancermentioning
confidence: 99%
“…However, the incidence increases with concomitant spinal cord injuries particularly in those with long-term catheters [1, 2]. …”
Section: Introductionmentioning
confidence: 99%